Modeling dynamic capabilities in their logical sequence and relation to performance - Aminu, Mohammed Ibrahim; Mahmood, Rosli (Medwell Journal, 2016)
Although, resource-based is a potential approach to the explanation of how firms use their idiosyncratic valuable intangible resources to conceive of and implement value-creating strategy, the perspective has lapsed on the explanation of how and why firms outperform others in rapid changing environments.Ths laid to the emergence of dynamic capabilities view as an extension of the former.Neveheless, hitherto the concept of dynamic capabilities is yet to be well acquainted. Hence, this research has purposely reviewed the concept of dynamic capabilities and conceptually developed a model which hypothesized the possible relationships between various phases of dynamic capabilities (ie, sensing, leaning,integrating and coordinating capabilities) as well as their role as potential antecedents of performance.The study has concluded that there is a positive conceptual relationship between one capability to another in their logical sequence and also all capabilities positively relate to performance. Future, research may found this model important to investigate such relationships empirically.